Traveling Wave Phenomena in Modeling of Lightning Threat to Equipment during Direct Strike to the Tower of GSM Base Station - Markowska, R.; Sowa, A. W. (Elektronika ir Elektrotechnika, 2013)
This paper deals with application of electromagnetic field theory and method of moments in analysis of lightning threat during direct strike to the tower of a GSM base station. The object is to elaborate analytical formulas and parameters for the waveforms of source current which would allow the natural traveling wave processes to be properly accounted for in the calculation results. These waveforms were estimated using numerical modeling. Based on these results, the computations, with the same numerical method, were performed in order to evaluate the level of lightning threat to the equipment of the GSM base station. DOI: http://dx.doi.org/10.5755/j01.eee.19.7.5160